2017
DOI: 10.1016/j.nahs.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Gossip based asynchronous and randomized distributed task assignment with guaranteed performance on heterogeneous networks

Abstract: The main contribution of this paper is a novel distributed algorithm based on asynchronous and randomized local interactions, i.e., gossip based, for task assignment on heterogeneous networks. We consider a set of tasks with heterogeneous cost to be assigned to a set of nodes with heterogeneous execution speed and interconnected by a network with unknown topology represented by an undirected graph. Our objective is to minimize the execution time of the set of tasks by the networked system. We propose a local i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To study network consensus in strongly connected networks, Wu et al [30] presented a gossip-based algorithm and showed it could quickly reach consensus as well as reducing the consumed transmissions. Franceschelli et al [31] studied the execution time of heterogeneous tasks in an undirected graph. They proposed randomised interaction algorithm based on gossip to let the nodes cooperatively complete the tasks to minimise the task execution time.…”
Section: Average Consensus Problem In Wireless Networkmentioning
confidence: 99%
“…To study network consensus in strongly connected networks, Wu et al [30] presented a gossip-based algorithm and showed it could quickly reach consensus as well as reducing the consumed transmissions. Franceschelli et al [31] studied the execution time of heterogeneous tasks in an undirected graph. They proposed randomised interaction algorithm based on gossip to let the nodes cooperatively complete the tasks to minimise the task execution time.…”
Section: Average Consensus Problem In Wireless Networkmentioning
confidence: 99%
“…Other related discrete path planning solutions are presented in [7], [8], where the authors assume tasks combining Boolean variables on the graph nodes and define a new language as an extension of the Generalized Traveling Salesman Problem for final system states, and in [15], [16], [17], where MILP (Mixed ILP) techniques were proposed for solving different planning or allocation problems in a centralized or distributed fashion. With respect to these works, our method allows Boolean specifications also on robot trajectories, not only on the system final states.…”
Section: Related Workmentioning
confidence: 99%